(untitled) (Sciences & Technology. A, exactes sciences, 2017)
We present a space-time transformation to the harmonic oscillator with a time-dependent mass and frequency and we transform the problem to that of constant mass and time-dependent potential of the form . The propagator and the corresponding wave functions are given. A new general model of time-dependent mass is proposed.